2016
DOI: 10.1128/jvi.02737-15
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Nuclear Antigen 3 (EBNA3) Proteins Regulate EBNA2 Binding to Distinct RBPJ Genomic Sites

Abstract: Latent infection of B lymphocytes by Epstein-Barr virus (EBV) in vitro results in their immortalization into lymphoblastoid cell lines (LCLs); this latency program is controlled by the EBNA2 viral transcriptional activator, which targets promoters via RBPJ, a DNA binding protein in the Notch signaling pathway. Three other EBNA3 proteins (EBNA3A, EBNA3B, and EBNA3C) interact with RBPJ to regulate cell gene expression. The mechanism by which EBNAs regulate different genes via RBPJ remains unclear. Our chromatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 61 publications
2
52
0
Order By: Relevance
“…ChIP-seq analysis shows that EBNA2 and EBNA3s (EBNA3A, EBNA3B, and EBNA3C) can target multiple cellular genes through cell-specific regulation of long-range enhancer-promoter interactions [56]. Another study indicated that while these four latent antigens can competitively bind to RBPJκ at its repressive sites to control cellular genes expression, EBNA3s are more likely to interact with other transcription factors [57]. For example, IRF4 is essential for EBNA3C to associate with specific sites on viral and cellular DNA [16, 55, 57, 58].…”
Section: 3 Molecular Biology Of Ebv-mediated B-cell Lymphomasmentioning
confidence: 99%
See 1 more Smart Citation
“…ChIP-seq analysis shows that EBNA2 and EBNA3s (EBNA3A, EBNA3B, and EBNA3C) can target multiple cellular genes through cell-specific regulation of long-range enhancer-promoter interactions [56]. Another study indicated that while these four latent antigens can competitively bind to RBPJκ at its repressive sites to control cellular genes expression, EBNA3s are more likely to interact with other transcription factors [57]. For example, IRF4 is essential for EBNA3C to associate with specific sites on viral and cellular DNA [16, 55, 57, 58].…”
Section: 3 Molecular Biology Of Ebv-mediated B-cell Lymphomasmentioning
confidence: 99%
“…Another study indicated that while these four latent antigens can competitively bind to RBPJκ at its repressive sites to control cellular genes expression, EBNA3s are more likely to interact with other transcription factors [57]. For example, IRF4 is essential for EBNA3C to associate with specific sites on viral and cellular DNA [16, 55, 57, 58]. A recent study identified a number of host dependency factors in BL and LCLs using CRISPR/Cas9 loss-of-function screen [59].…”
Section: 3 Molecular Biology Of Ebv-mediated B-cell Lymphomasmentioning
confidence: 99%
“…EBNALP binds preferentially to promoters than enhancers, and co-activates with EBNA2 by removing transcription repressors, including N-CoR, from EBNA2 (Harada and Kieff, 1997; Ling et al, 2005; Portal et al, 2011; Portal et al, 2013). EBNA3A and 3C can be tethered to DNA through cell TFs including IRF4 and BATF (Banerjee et al, 2013; Jiang et al, 2014; Schmidt et al, 2015; Wang et al, 2015). EBNA3A and 3C repress both p14 ARF and p16 INK4A , thereby preventing cell senescence (Maruo et al, 2006; Skalska et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, EBNA3 ChIP-seq experiments have been performed previously and thousands of EBNA3 binding sites have been identified (24,2729). These studies have been very informative, each an improvement on the previous, as reagents and resources have become available.…”
Section: Introductionmentioning
confidence: 99%